Exploratory study on the adoption of knowledge management practices in small medium enterprises in resource constrained areas - Twongyirwe, Theodora Mwebesa; Lubega, Jude (International Conference on Knowledge Management and Information Sharing, 2018)
The aim of this paper is to shed light on Knowledge Management (KM) practices in Small Medium enterprises (SMEs) in resource constrained areas. The Paper presents the results of an exploratory study investigating the adoption of KM practices in 66 enterprises across the Dairy industry located in South western Uganda. The Methodology adopted focused on literature review to gain an in-depth understanding KM in SMEs and insight into the Dairy industry in Uganda, a structured questionnaire was used to collect information from the different stakeholders and an interview guide used to conduct interviews with various stakeholders in the firms. The results show that SMEs are falling behind large companies in developing KM practices; however all the firms showed a significant understanding of the benefits of KM. There is significantly low skills and usage of ICT in SMEs which is essential for successful implementation of KM within an organization. Web browsing, voice and SMS are the most commonly used ICT Services and the least used are ICT professional services like business intelligence tools, ERPs and Dashboards, which creates significant opportunity fordevelopment of KM tools suitable for resource constrained areas. Skills gap, informalknowledge and technological barriers where highlighted as significant barriers to implementation of KM. There is limited usage of Decision Support Systems and Data mining tools as KM Tools.
Keywords: Knowledge Management (KM); Small Medium Enterprises (SMEs).